An Overview of Two-Component Signal Transduction Systems Implicated in Extra-Intestinal Pathogenic E. coli Infections - Breland, Erin J.; Eberly, Allison R.; Hadjifrangiskou, Maria (Frontiers in Cellular and Infection Microbiology, 2017)
Extra-intestinal pathogenic E. coli (ExPEC) infections are common in mammals and birds. The predominant ExPEC types are avian pathogenic E. coli (APEC), neonatal meningitis causing E. coli/meningitis associated E. coli (NMEC/MAEC), and uropathogenic E. coli (UPEC). Many reviews have described current knowledge on ExPEC infection strategies and virulence factors, especially for UPEC. However, surprisingly little has been reported on the regulatory modules that have been identified as critical in ExPEC pathogenesis. Two-component systems comprise the predominant method by which bacteria respond to changing environments and play significant roles in modulating bacterial fitness in diverse niches. Recent studies have highlighted the potential of manipulating signal transduction system function as a means to chemically re-wire bacterial pathogens, thereby reducing selective pressure and avoiding the emergence of antibiotic resistance. This review begins by providing a brief introduction to characterized infection strategies and common virulence factors among APEC, NMEC, and UPEC and continues with a comprehensive overview of two-component signal transduction networks that have been shown to influence ExPEC pathogenesis.